THE ROLE OF THE COOPERATIVE SCRIPT METHOD IN DEVELOPING SELF-CONFIDENCE AND PUBLIC SPEAKING SKILLS AMONG MADRASAH IBTIDAIYYAH STUDENT - Anshori, Isa; Majid, M. Rofiqul; Fitria, Sufatul; Haq, Ghazwu Fikril (Jurnal Pendidikan Islam, 2024)
The Cooperative Script Method (CSM) has gained prominence as an instructional approach that enhances key student skills, including self-confidence and public speaking abilities. This study aimed to investigate the impact of CSM on students' self-confidence and public speaking skills. The research was conducted at Madrasah Ibtidaiyah Al-Anwar Sarang using a quantitative approach, involving 37 purposively selected fifth-grade students. Data were collected through questionnaires, complemented by in-depth observations, and analyzed using linear regression and the Sobel test. The results indicated that CSM significantly enhances students' self-confidence (p